Woven Bracelet Training with Economic Value in LPK Children TK II Pontianak - diana fitriani (STMIK Pontianak, 2020)
Every human being has the possibility to make mistakes, but each human being also has the opportunity to change to be better. The assisted children in LPKA TK II Pontianak are an example of how many criminal incidents involving underage children. The mistakes made are not purely their faults. The role of parents and society should be the key to the increasingly widespread crime among children. Based on this understanding, training is the best contribution to saving their future and will be able to work. An economical woven bracelet training is considered appropriate because it does not require large capital to start a business. The training activities are summarized in the Tri Dharma of Higher Education activities, namely community service. The results of this training are knowledge of the process of weaving bracelets starting from preparing materials for every one-time production then the main process until the bracelets are packaged and ready to be marketed. This briefing aims to enrich the repertoire of the skills of fostered children so that if one day they leave the institution, they have the desire and capital to continue to live with positive activities